Recent Insights on Drug Delivery System in Hypertension: From Bench to Market - Sharma, Gaurav; Sharma, Abhishek (Current Hypertension Reviews, 2023)
Hypertension is a significant hazardous aspect for several diseases, like cardiovascular disease, kidney failure, and brain disease. Hypertension has become the most lethal condition globally, affecting approximately 1 billion people aged around 30-79 years worldwide. In the year 2022, India was ranked 170th for men and 193rd for women for HTN diagnosis rates among 200 countries worldwide. The main risk factor for cardiac failure and stroke is hypertension. The conventional classes of antihypertensive medications currently available have some side effects. Previously, hypertension has been discussed by various researchers using conventional drug-targeting methods such as ACE inhibitors, aldosterone inhibitors, or renin inhibitors. Recently, novel drug delivery technologies utilizing nanoparticles and new pharmacological classes like ACE2 and APA inhibitors have been studied for the medication of hypertension. In this review, we have covered the epidemiology of hypertension in India, its pathophysiology, medications used in the management of hypertension using nanotechnology, and antihypertensive drugs currently available in the market that are approved and patented. Finally, we have covered how hypertension can be managed with the help of smart devices and artificial intelligence (AI) for improved therapy.
Keywords: artificial intelligence